Individual and combined lethal toxicity of pesticide combination on the juveniles of Rohu Labeo Rohita (HAM) - Vinita P Nair (Department of Fishery Biology, College of Fisheries, 2003)
In the natural aquatic ecosystems, fishes are exposed to more than one biocide or contaminant at a given time. In the present study an attempt is made to understand the individual and combined toxicity of the common biocides- malathion, methyl parathion, endosulfan and 2,4- D on the juveniles of rohu (Labeo rohita) under laboratory conditions. The 48-h LCso values were computed based on the probit analysis method of Finney (1971). The 48-h LCso value of malathion was 7.89 mg.l" (7.28 to 8.61); methyl parathion was 7.34 mg.l" (7.25 to 7.43); endosulfan was 0.0036 mg.l" (0.0025 to 0.0047) and 2,4-D was 962.43 rng.l" (954.02 to 970.81). The 'additive index' values and 'magnification factors' for the combined toxicity were calculated for the different pesticide pairs based on the method of Marking (1977). For 2,4-D-malathion it was -0.018 (-0.09 to 0.50) and xO.98 (0.91 to 1.05) respectively; for 2,4-D-methyl parathion it was 0.218 (-0.02 to 0.40) and x1.22 (0.98 to 1.40) respectively; for 2,4-D-endosulfan it was -0.073 (- 0.40 to 0.16) and xO.93 (0.60 to 1.16) respectively; for malathion-methyl parathion it was 0.24 (0.021 to 0.53) and x1.24 (1.0214 to 1.53) respectively and [or malathion-endosulfan it was 1.648 (0.74 to 2.93) and x2.65 (1.74 to 3.98) respectively. Individually it is found that 2,4-D (chlorophenoxy herbicide) is 'moderately toxic', malathion and methyl parathion (organophosphate insecticides) are 'toxic' and endosulfan (organochlorine insecticide) is 'very toxic' to juveniles of rohu under t ' stc£c with renewal 48-h LCso test. But the 'strictly additive' nature of the insecticide-weedicide combinations and the 'more than additive' nature of the insecticide pairs coupled with the sequential or even simultaneous application of these chemicals in the paddy fields and plantations increase the potential [or pollution of these pesticides in the freshwater and coastal ecosystem of the State. Chronic combined sublethal toxicity